WIRAUSAHA BERBASIS RUMAH TANGGA (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2014)
Entrepreneurship is the work done by themselves to produce something that can add value to earnings. Entrepreneurship means having or doing business that can provide value-added income. Entrepreneurial mostly done by the community from various circles. The work done is also diverse and creative abilities possessed by a person or group of people. The entrepreneurship skills many are carried out by mother-housewife. Ability possessed by these mothers are usually the capabilities of talent, hobby or inheritance. Ibu Kartini who has a business in the manufacture of snack marning highly preferred by people Sumberejo Village, District Ambulu, Jember. This snack cake into one dish widths. The work done since 30 years ago, originally done on the basis to supplement the family income. This business is still traditional in nature and done independently and not be a legacy for their children. Jamie's mother is a businesswoman households in the same village with Ibu Kartini, producing cakes are usually ordered community about events for celebration or slametan. The efforts made since 15 years ago. This effort evolved with the number of orders from the surrounding community. However, this business is still conducted independently without any plan to pass the business to their children. The second attempt by two mothers is an example of an independent entrepreneur to supplement the family income. The work done by the system of production and management is still traditional family is still limited in scope countryside.